Kinetics of domain growth in Ising systems with bond disorder at regularly selected sites - Singh A. (My University, 2025)
We study the structure, phase behaviour and growth laws in Ising ferromagnets and binary mixtures with bond disorder introduced at regularly selected sites for a critical quench. The results presented here are from extensive Monte Carlo simulations on two-dimensional Ising systems. Domain growth in a ferromagnet is modelled by using nonconserved spin-flip (Glauber) kinetics, and phase separation in a binary (AB) mixture is modelled by conserved spin-exchange (Kawasaki) kinetics. In both cases, we observed that the domain growth law is consistent with the respective power-law growth with the variable growth exponent that depends on the number of disordered sites. The nonconserved Ising system follows dynamical scaling for all the number of disordered sites studied here; however, a small deviation is noticed for r→ 0 at a large number of disordered sites. Whereas, for the conserved case, dynamical scaling deviates from the master curve after a reasonable number of disordered lattice sites; we notice the formation of lamellar evolution morphology at a higher number of disordered sites at later times. © 2020, Indian Academy of Sciences.